Hacia una caracterización del docente universitario “excelente”: Una revisión a los aportes de la investigación sobre el desempeño del docente universitario - Francis Salazar, Susan (2012)
This article presents an analysis of the qualities of an effective college professor. The analysis emerges from research on the professor’s performance assessment. In conducting this type of research, it is possible to identify two tendencies: (1) a reflection and essay articles about the profiles of effectiveness and (2) research and performance assessment process. The focus is on the latter tendency in order to find out the basis to for understand the college professors´ action in their relationship with the context The analysis of these studies at least shows two categories: the professor’s multi-dimension and historical and contextual value of qualities that make this professor effective. The first tendency seeks to reveal the interrelation between the personal, disciplinary and pedagogical scopes. The third scope is very important in terms of the research on orientations in the process of training college professors.